Hydrogen peroxide toxicity of a lower lip piercing: A case report - Monique Graf; Craig Reece Brockman, II; Kara Pretzlaff (JEM Reports)
Background: Hydrogen peroxide, a well-known cleaning product, is responsible for a large number of emergency department visits each year. The current literature contains only few case reports of these exposures, and our case report provides an example of what can happen from direct hydrogen exposure and how it is managed from the emergency department. Case report: A 26-year-old female presented to the emergency department with lower lip swelling and overlying skin changes. Vital signs were within normal limits and the remainder of her exam was within normal limits. It was elicited with further questioning that the patient had irrigated her lip piercing the night before with hydrogen peroxide. With this information, the correct diagnosis of hydrogen peroxide toxicity was made and with the help of oral and maxillofacial surgery, the patient was treated appropriately for this condition. Why should emergency medicine physicians be aware of this: Toxic exposures, whether via direct contact, inhalation, or ingestion, are commonly seen in the emergency department and require expeditious diagnosis and treatment. Based on physical exam alone, lip swelling suggests a variety of diagnoses. In this case, as in many others, accurate history taking is crucial in making the correct diagnoses.